O INIMIGO DO POETA COMO UM MACACO - Corrêa, Paula da Cunha (Organon, 2012)
A study of the the fable of the Fox and the Ape (Aesop 38 Chambry, 81 Perry?) narrated inthe iambi of Archilochus. The commentary on the fragments (Arch. 185-187W) discusses their ancientsources, textual difficulties, and the modern reconstructions of Archilochus’ “ainos” via Aesop andBabrius (a). The “ethos” of the fox and of the ape in antiquity, examined in section b), illuminates themanner in which the poet attacks his enemy in this iambus.